Allopurinol reduces brachial and central blood pressure, and carotid intima-media thickness progression after ischaemic stroke and transient ischaemic attack: a randomised controlled trial. Issue 14 (1st May 2014) - Higgins, P; Walters, M R; Murray, H M; McArthur, K; McConnachie, A; Lees, K R; Dawson, J
Abstract : Objective: Central blood pressure (CBP) and carotid intima-media thickness (CIMT) are surrogate measures of cardiovascular risk. Allopurinol reduces serum uric acid and oxidative stress and improves endothelial function and may therefore reduce CBP and CIMT progression. This study sought to ascertain whether allopurinol reduces CBP, arterial stiffness and CIMT progression in patients with ischaemic stroke or transient ischaemic attack (TIA). Methods: We performed a randomised, double-blind, placebo-controlled study, examining the effect of 1-year treatment with allopurinol (300 mg daily), on change in CBP, arterial stiffness and CIMT progression at 1 year and change in endothelial function and circulating inflammatory markers at 6 months. Patients aged over 18 years with recent ischaemic stroke or TIA were eligible. Results: Eighty participants were recruited, mean age 67.8 years (SD 9.4). Systolic CBP [−6.6 mm Hg (95% CI −13.0 to −0.3), p=0.042] and augmentation index [−4.4% (95% CI −7.9 to −1.0), p=0.013] were each lower following allopurinol treatment compared with placebo at 12 months. Progression in mean common CIMT at 1 year was less in allopurinol-treated patients compared with placebo [between-group difference [−0.097 mm (95% CI −0.175 to −0.019), p=0.015]. No difference was observed for measures of endothelial function. Conclusions: Allopurinol lowered CBP and reduced CIMT progression at 1 year compared with placebo in patients with recent ischaemic stroke and TIA. This extends the evidence of sustained beneficial effects of allopurinol to these prognostically significant outcomes and to the stroke population, highlighting the potential for reduction in cardiovascular events with this treatment strategy. Trial registration number: ISRCTN11970568.